The Dynamics of Qatar’s Perspective on LGBTQ Issues during World Cup 2022 - Ramdan Lamato; Muhammad Abdul Azis (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This paper examines the influence of Qatar’s Islamic identity on its policies during the 2022 FIFA World Cup, with a focus on LGBTQ rights. Using a constructivist approach, the study explores how Qatar’s adherence to Islamic principles, particularly Sharia law, shaped its regulations and responses to international pressures. Qatar's prohibition of LGBTQ symbols, despite assurances of safety for all attendees, including the LGBTQ community, drew significant criticism from Western nations and human rights organizations. The study highlights the tension between Qatar’s cultural and religious values and global expectations surrounding inclusivity and human rights. It also explores the broader implications of Qatar’s policies, reflecting its challenge of balancing traditional Islamic values while hosting a global event. Ultimately, this research sheds light on the complexities of cultural diplomacy and the difficulties nations like Qatar face in navigating conflicting global and local norms.